ORGANIZATIONAL LEADERSHIP DRIVER AFFECT PERFORMANCE OF THE TOURISM STATE OWNED CORPORATIONS IN KENYA - Muthoka, Miriam; Oloko, Dr.Margaret; Obonyo, Dr. Levi (European Journal of Business and Strategic Management, 2017)
Purpose: This study sought to provide an opportunity to test organizational leadership driver on performance of the tourism state owned corporations in Kenya. Methodology:The study employed descriptive and cross-sectional research designs. The target population comprised all the Tourism state owned corporations in Kenya with the management of these firms being the respondents. A census study was carried out due to small nature of the target population. Data collection involved the use of questionnaires which attracted both quantitative and qualitative responses. The questionnaires were administered through drop and pick method. The respondents were all the Chairmen, CEO, managers and assistant managers of all Tourism state corporations in Kenya.These data was analyzed using content analysis for qualitative data. The quantitative data was analyzed using regression analysis. ANOVA test was carried out to test the significance of the model. Results:The results showed that most organizations give room for contingent rewards to its employees. Further results indicated that indicated that Individual characteristics, Idealized influence, Inspirational motivation, Intellectual stimulation and command and Control affect performance of the organization to a great extent. The results also showed that individualized influence, intellectual stimulation and practicing command and control are positively and significantly related to performance of tourism organizations. The regression results indicated that organizational leadership driverwas positively correlated to organization performance and it explains 29.1% of the changes in performance of the organizations. Organizational leadership driver was established to have a positive and significant effect on performance in the Tourism state corporations in Kenya. Policy recommendation:The study recommended that Tourism state corporations in Kenya should have measures to adopt Individual characteristics, Idealized influence, Inspirational motivation, Intellectual stimulation among their leaders and command and Control.